VISIONARY LEADERSHIP IN EDUCATION MANAGEMENT: LEADING TOWARD OPTIMAL ACHIEVEMENT IN THE ERA OF INDEPENDENT LEARNING - Ratri Candrasari; Yorman; Nanny Mayasari; Rasty Yulia; Floribertha Lake (Indonesian Journal of Education (INJOE), 2023)
This study aims to investigate the role of visionary leadership in education management to achieve optimal performance in the Merdeka Belajar era. In education that continues to develop with dynamic changes, visionary leadership is an essential factor in directing educational institutions to success. The research method used is qualitative, collecting data through in-depth interviews, participatory observation, and document analysis. Respondents to this study consisted of school principals, teachers, students, and parents in several schools that have implemented the Free Learning concept. The research results show that visionary leadership creates an innovative learning environment and motivates education stakeholders. Theoretical school principals can describe and communicate a clear vision effectively to all school members. They can also identify opportunities and challenges in the Freedom to Learn era and take proactive steps to improve the quality of education. In addition, visionary leadership encourages the active participation of all education stakeholders, such as teachers, students, and parents. They involve them in decision-making and provide space for initiative and experimentation in learning. This creates a positive climate in the school and encourages productive collaboration. In conclusion, visionary leadership is essential in achieving optimal performance in the Merdeka Belajar era. Theoretical school principals can lead Change, motivate, and involve all education stakeholders to achieve the desired goals. This research further  explains  the  importance  of  visionary  leadership  in  education management in a constantly evolving era. The implication is that educational leaders need to develop creative leadership skills and apply them in a dynamic educational context